Ecological comparative study of the rock-rose scrubs of Madrid, II. Soil-pH seasonal fluctuation - Moreno, José Manuel (Lazaroa, 2014)
During twao years soil and litter pH of 31 permanent plots grown by several rock-rose scrubs (jarales) of Cistion laurifolii at different dynamic stages have been measured. Acidily records show the existence of important seasonal variations and according to a certain rythm. The different syntaxa are characterized as for this ecological factor and the results for these matorrals are compared with other data of heath-scrubs. Adult jaral-phases tend to decrease soil pH when compared with younger dwarf-scrubs-phases, nevertheless upper soil levels generally remain less acidic. Multivariable analysis do not show preference of t he different syntaxa for a certain soil-pH range.